A Historic Case of Cardiac Surgery in Pregnancy - Said Benlamkaddem; Adnane Berdai; Smael Labib; Mustapha Harandou (Hindawi Limited, 2016)
Background. Heart disease is the leading cause of nonobstetric mortality in pregnant women. Because of high risk, medical management represents the first line of treatment. However, when medical treatment fails, cardiac surgery becomes necessary. Case Presentation. A 27-year-old female who underwent successfully cardiac surgery three times within 3 years. At the first time, she had an aortic valve replacement at 25 weeks of gestation after an infectious endocarditis complicated with an ischemic stroke. At 39 weeks of gestation, she had delivered, vaginally, a healthy baby boy weighing 2800 g. In the second time, pregnant again at 30 weeks of gestation, she had a mitral valve replacement with an aortic prosthesis reinforcement after a paraprosthetic regurgitation and a mitral vegetation. A fetal death in utero had occurred; the extraction of the fetus by cesarean section with a tubal ligation was performed after stabilization of the mother. In the third time, she underwent successfully a mitral prosthesis replacement with Bentall's procedure after a mitral prosthesis disinsertion with an abscess of aortic annulus due to new episode of infectious endocarditis. Conclusion. Our patient has assembled almost all poor prognosis factors, which makes her a real historic case, probably never described in the literature.